Clinical standards for the management of adverse effects during treatment for TB - Singh, K P; Carvalho, A C C; Centis, R; D Ambrosio, L; Migliori, G B; Mpagama, S G; Nguyen, B C; Aarnoutse, R E; Aleksa, A; van Altena, R; Bhavani, P K; Bolhuis, M S; et al. (The international journal of tuberculosis and lung disease, 2023)
Adverse effects (AE) to TB treatment cause morbidity, mortality and treatment interruption. The aim of these clinical standards is to encourage best practise for the diagnosis and management of AE. 65/81 invited experts participated in a Delphi process using a 5-point Likert scale to score draft standards. We identified eight clinical standards. Each person commencing treatment for TB should: Standard 1, be counselled regarding AE before and during treatment; Standard 2, be evaluated for factors that might increase AE risk with regular review to actively identify and manage these; Standard 3, when AE occur, carefully assessed and possible allergic or hypersensitivity reactions considered; Standard 4, receive appropriate care to minimise morbidity and mortality associated with AE; Standard 5, be restarted on TB drugs after a serious AE according to a standardised protocol that includes active drug safety monitoring. In addition: Standard 6, healthcare workers should be trained on AE including how to counsel people undertaking TB treatment, as well as active AE monitoring and management; Standard 7, there should be active AE monitoring and reporting for all new TB drugs and regimens; and Standard 8, knowledge gaps identified from active AE monitoring should be systematically addressed through clinical research. These standards provide a person-centred, consensus-based approach to minimise the impact of AE during TB treatment.